Perceptions of stalking: a comparison of the prior-relationship misconception and perceptions of threat for transgender and cisgender perpetrators - Cook, Lydia Caroline (2020)
Stalking literature has identified prior-relationship and gender misconceptions that see stranger and male perpetrators perceived as more threatening than ex-partner or female perpetrators. These perceptions do not reflect the reality. The present study seeks to build on stalking misconception literature by comparing perceptions of transgender and cisgender perpetrators. This study utilised an experimental, mixed-level two-factor design, comprised of ‘Perpetrator Gender’ (Cisgender Male x Transgender Female x Transgender Male) and ‘Prior Relationship’ (Ex-partner x Stranger). 501 participants were presented with one of six vignettes, and responded to scale items concerning threat, risk of violence and the need for police intervention. Main effect analyses revealed significant differences in perceptions of threat between stranger and ex-partner perpetrators, and between cisgender and transgender perpetrators. No significant differences were found in perceptions of threat for transgender female and transgender male perpetrators. Interaction effects revealed that the prior-relationship misconception was not influenced by perpetrator gender identification. Forensic implications include specialised training of police, and the inclusion of stalking victims in domestic violence support services. Broader societal implications focus on the representations of stalking in the media. Limitations and suggestions for future research are discussed.